Analysis of Small Ubiquitin-Like Modifier (SUMO) Targets Reflects the Essential Nature of Protein SUMOylation and Provides Insight to Elucidate the Role of SUMO in Plant Development. Issue 2 (28th August 2015) - Elrouby, Nabil
Abstract : Analysis of the mechanisms, regulation, and consequences of protein SUMOylation in plants and other eukaryotes highlights the conservation and importance of this process across taxa. Abstract: Posttranslational modification of proteins by small ubiquitin-like modifier (SUMO) has received much attention, reflected by a flood of recent studies implicating SUMO in a wide range of cellular and molecular activities, many of which are conserved throughout eukaryotes. Whereas most of these studies were performed in vitro or in single cells, plants provide an excellent system to study the role of SUMO at the developmental level. Consistent with its essential roles during plant development, mutations of the basic SUMOylation machinery in Arabidopsis ( Arabidopsis thaliana ) cause embryo stage arrest or major developmental defects due to perturbation of the dynamics of target SUMOylation. Efforts to identify SUMO protein targets in Arabidopsis have been modest; however, recent success in identifying thousands of human SUMO targets using unique experimental designs can potentially help identify plant SUMO targets more efficiently. Here, known Arabidopsis SUMO targets are reevaluated, and potential approaches to dissect the roles of SUMO in plant development are discussed.